Case report: Solitary mass of the sciatic nerve confirmed as a primary extranodal manifestation of diffuse large B-cell lymphoma in a geriatric patient - Becker, Hannes; Vogelsberg, Antonio; Feucht, Daniel; Estler, Arne; Tafrali, Deniz; Schittenhelm, Jens; Milla, Jakob; Kurz, Sylvia; Fend, Falko; Tatagiba, Marcos; Schuhmann, Martin U.; Hurth, Helene (Frontiers in Oncology, 2024)
Background: Neoplastic lesions affecting peripheral nerves are rare in the general population and, most often, are benign peripheral nerve sheath tumors. However, a minority of lesions represent high-grade malignancies associated with a poor prognosis, such as malignant peripheral nerve sheath tumors (MPNSTs). Very rarely, these tumors represent peripheral non-nerve sheath tumors (PNNSTs), such as hematological neoplasms that impair nerve function. These can be hard to distinguish from MPNSTs and other lesions arising from the nerve itself. In the present case report, we describe a rare case of direct infiltration of nerves by tumor cells of a hematological neoplasm. Methods: We report the case of a 90-year-old woman with acute onset of right-sided foot palsy, sensory loss, and pain, caused by an extensive solitary mass of the sciatic nerve in the thigh. We present and discuss the clinical presentation, multimodal diagnostic procedures, and treatment. Results: MRI of the right thigh and the caudal pelvis revealed a contrast-enhancing lesion infiltrating the sciatic nerve. Additionally performed staging imaging was non-revealing. After multidisciplinary discussion in the neuro-oncology tumor board, a MPNST was suspected and the patient underwent radical tumor resection. However, final histopathology revealed a diffuse large B-cell lymphoma (DLBCL). The patient received adjuvant palliative local radiotherapy which led to acceptable symptom control. Conclusions: Rare PNNSTs, including extranodal manifestationsof DLBCL can have similar clinical and radiological diagnostical features as PNSTs. Comprehensive diagnostic workup of contrast-enhancing lesions affecting peripheral nerves including MRI and metabolic imaging are recommended. Discussion in interdisciplinary tumor boards facilitates finding individual treatment approaches.